2002
DOI: 10.1073/pnas.242579699
|View full text |Cite
|
Sign up to set email alerts
|

Microarray-based detection and genotyping of viral pathogens

Abstract: The detection of viral pathogens is of critical importance in biology, medicine, and agriculture. Unfortunately, existing techniques to screen for a broad spectrum of viruses suffer from severe limitations. To facilitate the comprehensive and unbiased analysis of viral prevalence in a given biological setting, we have developed a genomic strategy for highly parallel viral screening. The cornerstone of this approach is a long oligonucleotide (70-mer) DNA microarray capable of simultaneously detecting hundreds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
243
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 694 publications
(252 citation statements)
references
References 22 publications
2
243
0
Order By: Relevance
“…Pathogen concentrations obtained with this system could then be used for quantitative microbial risk assessment (QMRA) (19). Several advantages of this MFQPCR over other simultaneous multipathogen detection technologies such as microarray (20,21), TaqMan array (22,23), Luminex assay (24), OpenArray (25), FilmArray (26), and molecular inversion probe assay (27) include its high sensitivity and quantitative performance. However, MFQPCR technology has not been applied to quantify multiple viral pathogens.…”
mentioning
confidence: 99%
“…Pathogen concentrations obtained with this system could then be used for quantitative microbial risk assessment (QMRA) (19). Several advantages of this MFQPCR over other simultaneous multipathogen detection technologies such as microarray (20,21), TaqMan array (22,23), Luminex assay (24), OpenArray (25), FilmArray (26), and molecular inversion probe assay (27) include its high sensitivity and quantitative performance. However, MFQPCR technology has not been applied to quantify multiple viral pathogens.…”
mentioning
confidence: 99%
“…Several studies have reported the use of DNA microarrays for the detection or classification of influenza viruses (26)(27)(28)(29)(30)(31). These microarrays were designed to detect specific influenza A virus strains (29,30) or to subtype and pathotype the HA of avian influenza viruses (30) but not to determine both the HA and NA subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…In designing probes for our array, we sought to balance the goals of conservation and uniqueness, prioritizing oligo sequences that were conserved, to the extent possible, within the family of the targeted organism, and unique relative to other families and kingdoms. We designed arrays with larger numbers of probes per sequence (50 or more for viruses, 15 or more for bacteria) than previous arrays having only [2][3][4][5][6][7][8][9][10] probes per target (5,6). The large number of probes per target was expected to improve sensitivity, an important consideration given possible amplification bias in the random PCR sample preparation protocol, which could result in non-amplification of genome regions targeted by some probes.…”
Section: Llmda Probe Design For Broad Spectrum Detection Of Viruses Amentioning
confidence: 99%